Co-influence of nanofiller content and 3D printing parameters on mechanical properties of thermoplastic Polyurethane (TPU)/halloysite nanotube (HNT) nanocomposites - Nugroho, Wendy Triadji; Dong, Yu; Pramanik, Alokesh; Zhang, Zhixiao; Ramakrishna, Seeram (MDPI AG, 2023)
Thermoplastic polyurethane (TPU) belongs to a polyurethane family that possesses an elongation much higher than 300%, despite having low mechanical strength, which can be overcome by incorporating clay-based halloysite nanotubes (HNTs) as additives to manufacture TPU/HNT nanocomposites. This paper focuses on the co-influence of HNT content and 3D printing parameters on the mechanical properties of 3D printed TPU/HNT nanocomposites in terms of tensile properties, hardness, and abrasion resistance via fused deposition modelling (FDM). The optimum factor-level combination for different responses was determined with the aid of robust statistical Taguchi design of experiments (DoEs). Material characterisation was also carried out to evaluate the surface morphology, nanofiller dispersion, chemical structure, thermal stability, and phase behaviour corresponding to the DoE results obtained. It is evidently shown that HNT level and infill density play a significant role in impacting mechanical properties of 3D-printed TPU/HNT nanocomposites.